The Application of Mental Hygiene Concept of Zakiah Daradjat for Adolescence in Educational Institutions (An Experience of Ruhama Islamic Foundation of Prof. Dr. Zakiah Daradjat) - Muhammad Nurrosyid Huda Setiawan; Asep Awaludin (At-Ta'dib, 2020)
Mental Hygiene is a branch of psychology that talks about the treatment of human mental health. One of the scientists who focuses on this field is Zakiah Daradjat. He succeeded in reformulating his mental hygiene concept so that it has its own characteristics. Not only speaking in theory, but he has also applied his concept in fostering community mental health in his home clinic and also formal educational institutions through the foundation he founded, namely the Islamic Foundation Ruhama. In his thesis, he is interested in researching the problems of adolescents in Indonesia. This is because adolescence is a transitional age from children to adults who need more attention in dealing with life problems. Formal education institutions become one of the mediators to play a big role in dealing with their problems. This research is interesting because the mental hygiene of zakiah daradjat is able to be a solution in dealing with adolescent problems that are applied through his formal education. This is grounded research by making the main research objects of Islamic Junior High School and Islamic Vocational High School Ruhama, South Tangerang. Data collection by interview and studying the curriculum in both schools. After conducting the research, it was found that the application of Zakiah Daradjat's mental hygiene concepts at the two high school institutions was successful and exemplary. This success is driven by three factors. First, there are mental hygiene values of zakiah daradjat which are in line with Pancasila. Second, attractive and innovative application methods. Third, holistic and integrative application techniques in the three education centers.